Addressing some of the technical challenges associated with liquid phase S/TEM studies of particle nucleation, growth and assembly. (March 2019) - Zhu, Guomin; Reiner, Holger; Cölfen, Helmut; De Yoreo, James J.
Highlights: Several beam artifacts in the Liquid phase TEM (LP-TEM) are dicussed. Methods to prevent the dissolution of oxides in the LP- TEM. Modifying solution and/or window chemistry to control the mobility of particles. Better controlled experiment by maintaining flow to LP-TEM and performing controlled heating. Abstract: In situ liquid phase scanning/ transmission electron microscopy (LP-S/TEM), enables direct observation of particle formation and evolution in the hydrated liquid state. Though powerful, this technique has significant technical limitations, which need to be carefully addressed in order to obtain reliable quantitative data. In this paper, we highlight several common challenges seen in LP-TEM, including electron-beam induced particle dissolution and motion, particle-membrane adhesion, contamination, and triggering of reactions. We describe our efforts to address these challenges by modifying solution and interface chemistry, maintaining solution flow, performing systematic post in situ analyses on the samples and applying controlled heating.